2022
DOI: 10.1007/s10071-022-01674-w
|View full text |Cite|
|
Sign up to set email alerts
|

Discrimination of cat-directed speech from human-directed speech in a population of indoor companion cats (Felis catus)

Abstract: In contemporary western cultures, most humans talk to their pet companions. Speech register addressed to companion animals shares common features with speech addressed to young children, which are distinct from the typical adult-directed speech (ADS). The way dogs respond to dog-directed speech (DDS) has raised scientists' interest. In contrast, much less is known about how cats perceive and respond to cat-directed speech (CDS). The primary aim of this study was to evaluate whether cats are more responsive to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 52 publications
1
4
1
Order By: Relevance
“…She compared the behavioral reactions of captive wolves, dogs, and hybrids of these two subspecies by using separate auditory stimulus patterns: motherese, normal speeches, and mute (no vocal stimuli), and recorded a strong preference of dogs for motherese, while wolves and wolf-dog hybrids showed no preference for any auditory stimulus over another. Our outcomes corroborate Hasting’s work [ 70 ] in regard to dogs’ reactions to high-pitched, intense speech, and points to a different pattern in wolves—a greater interest in low-pitched speeches—likely due to the lack in this subspecies of the domestication effects [ 71 ]. These results may be taken as a standpoint for future studies.…”
Section: Discussionsupporting
confidence: 89%
“…She compared the behavioral reactions of captive wolves, dogs, and hybrids of these two subspecies by using separate auditory stimulus patterns: motherese, normal speeches, and mute (no vocal stimuli), and recorded a strong preference of dogs for motherese, while wolves and wolf-dog hybrids showed no preference for any auditory stimulus over another. Our outcomes corroborate Hasting’s work [ 70 ] in regard to dogs’ reactions to high-pitched, intense speech, and points to a different pattern in wolves—a greater interest in low-pitched speeches—likely due to the lack in this subspecies of the domestication effects [ 71 ]. These results may be taken as a standpoint for future studies.…”
Section: Discussionsupporting
confidence: 89%
“…Working dogs showed better obedience to verbal stimuli given by familiar humans compared to strangers (Scandurra et al, 2017). A study by de Mouzon et al (2022) observed that cats respond to pet-directed speech only when addressed by their owner. Hence, it could be interesting to test the effect of the human pointer’s familiarity with the individual reindeer in further studies.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, it has been reported that cats transfer this intraspecific communicative behaviour when addressing communications to humans [40,43,44]. However, in previous studies investigating human-cat vocal communication, no tail-up displays were observed in response to human unimodal vocal signals, suggesting that unimodal vocal communication addressed by humans did not trigger visual communicative feedback in cats [8].…”
Section: Introductionmentioning
confidence: 90%
“…For many cats and dogs living in human environments, humans act as central partners, and companion animals often spend more time with humans than conspecifics [1,2]. Understanding the way our closest non-human companions perceive and react to their human environment is a contemporary topic which has drawn research attention in the past decade [1,[3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation